2014
DOI: 10.12659/msm.890749
|View full text |Cite
|
Sign up to set email alerts
|

Lack of usefulness of ureteral reconstruction with free bladder mucosa flap in dogs confirmed by microangiography

Abstract: BackgroundThere is a paucity of data addressing the blood supply in the surgically reconstructed ureter, and complete lack of microangiographic studies of the reconstructed ureter with the use of a free bladder mucosa flap. The present study evaluated the blood supply in the reconstructed dog ureter after a 5-centimeter segment resection, supplemented by a tube constructed from a free bladder mucosa flap.Material/MethodsFemale mongrel dogs (n=29) were used in this study. Under general anaesthesia, a 5-centimet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Furthermore, the authors supposed that the blood supply from periureteral connective tissues was sufficient to nourish the grafts, and the bladder has sufficient tissues for the required length of the neoureter regardless of the bladder capacity [ 50 ]. Kuzaka et al evaluated the blood supply of the ureters reconstructed with free bladder mucosa grafts by microangiography, and they found that the mucosa of the reconstructed portion of the ureters was completely regenerated, but there was an absence of revascularization and the regeneration of the muscular coat, which caused dense scarring or stricture of the ureters and massive periureteral fibrosis [ 51 ]. In addition, other problems may also arise, such as hypertrophy, prolapse, and a granulomatous reaction [ 52 , 53 ].…”
Section: Urogenital Grafts Ureteroplastymentioning
confidence: 99%
“…Furthermore, the authors supposed that the blood supply from periureteral connective tissues was sufficient to nourish the grafts, and the bladder has sufficient tissues for the required length of the neoureter regardless of the bladder capacity [ 50 ]. Kuzaka et al evaluated the blood supply of the ureters reconstructed with free bladder mucosa grafts by microangiography, and they found that the mucosa of the reconstructed portion of the ureters was completely regenerated, but there was an absence of revascularization and the regeneration of the muscular coat, which caused dense scarring or stricture of the ureters and massive periureteral fibrosis [ 51 ]. In addition, other problems may also arise, such as hypertrophy, prolapse, and a granulomatous reaction [ 52 , 53 ].…”
Section: Urogenital Grafts Ureteroplastymentioning
confidence: 99%